2020
DOI: 10.1101/2020.05.25.110908
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A developmental analysis of juxtavascular microglia dynamics and interactions with the vasculature

Abstract: Microglia, the resident macrophages of the central nervous system (CNS), are dynamic cells, constantly extending and retracting their processes as they contact and functionally regulate neurons and other glial cells. There is far less known about microglia-vascular interactions, particularly under healthy steady-state conditions. Here, we use the male and female mouse cerebral cortex to show that a higher percentage of microglia associate with the vasculature during the first week of postnatal development comp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Surprisingly, about 30% of brain resident microglia observed in adult mice are CAMs, resulting in a capillary-associated soma density that is higher than that of astrocytic cell bodies, but lower than pericyte cell body density. Electron microscopy further reveals that the myeloid cell bodies are closely associated with brain capillaries, localized outside the basement membrane that surrounds capillary endothelium, without any interposing astrocytic processes or endfeet consistent with a previous study 2 .…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Surprisingly, about 30% of brain resident microglia observed in adult mice are CAMs, resulting in a capillary-associated soma density that is higher than that of astrocytic cell bodies, but lower than pericyte cell body density. Electron microscopy further reveals that the myeloid cell bodies are closely associated with brain capillaries, localized outside the basement membrane that surrounds capillary endothelium, without any interposing astrocytic processes or endfeet consistent with a previous study 2 .…”
supporting
confidence: 89%
“…In a recent paper published in Nature Communications, Bisht et al identify a signalling mechanism that attracts and maintains microglia at the capillary wall. Moreover, they show that microglia regulate capillary vascular tone, playing a more significant role in blood flow regulation than previously thought.Microglia are the resident immune sentinels of the brain, responsible for the brain immune response as well as a variety of physiological functions including synapse pruning, neuronal regulation, and clearance of cellular and toxic debris [1][2][3][4] . However, much less is known about microglia-vascular interactions, particularly under healthy steady-state conditions.Recent studies using live 2-photon imaging, confocal, expansion, super-resolution, and electron microscopy, suggested that microglia associate with capillary vasculature at all ages and during central nervous system development, notably in areas lacking astrocyte endfoot coverage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, prior analyses did not consider cell-type specificity of the neuronal targets of microglial synapse pruning. Recent data have supported the notion that microglia are a heterogenous population of cells 62,63 , differing across brain regions and even within a brain region 62,64 . Here, we demonstrate that as a result of ELA, microglia engulf fewer synaptic elements of CRH+ neurons in the PVN (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…In the neonatal brain, higher percentage of microglia interact with vasculature in areas lacking astrocyte endfeet coverage, and the high motility of microglia along the vessel ceases when astrocyte endfeet more fully ensheath vessels after development of the brain. The timing of this microglia‐vascular interaction has been recently identified to be regulated by CX3CR1 17 …”
Section: The Cns Barriers As Age‐dependent Interfaces In Glia‐leucocyte Communicationsmentioning
confidence: 99%